Development of a new cellulose-based thermal insulating material (LACCEI, 2024)
Thermally insulating a body consists of preventing heat transfer from it to the outside and thus avoiding energy losses. The same principle can also be applied to enclosures in order to maintain a comfortable temperature inside the enclosure, which can be achieved by means of thermal insulation. However, the conventional thermal insulators used are often expensive and their production generates waste that pollutes the environment. For this reason, other alternatives have been sought, such as the manufacture of insulators from discarded organic materials, whose purpose is not only to preserve the temperature of the space, but also to have the necessary resistance so that it can be included in the infrastructure of a building. In this research, we have experimented the elaboration of these from newspaper and rice husks as a source of cellulose borax and glue. The samples obtained were tested for thermal conductivity, tension and compression tests, and it was found that they are effective in terms of thermal insulation, and also able to withstand a compressive stress of 21.23 (MPa) and a tensile stress of 1.73 (MPa). Based on these results, it can be deduced that recycled materials are a reliable option for the production of these components being an effective option for conserving and maintaining thermal energy in an enclosed space. Subsequently, it should be evaluated whether cellulose maintains both its strength and the properties studied in the future.